Relationship between family function and depression among caregivers of patients with acute pesticide poisoning: a cross-sectional study - Zixin Wen; Yanxia Zhang; Jie Shi; Yingying Zheng; Tianzi Jian; Xiangdong Jian; Baotian Kan (BMC Public Health)
Abstract Background Acute pesticide poisoning is a major public health concern. The relationship between family function and depression in caregivers of patients with acute pesticide poisoning is unclear. Therefore, this study aimed to explore the relationship between family function, coping style, and depression among caregivers of patients with acute pesticide poisoning and to provide a theoretical basis and intervention targets for future research. Methods A cross-sectional study was conducted among caregivers of patients with acute pesticide poisoning in the Department of Toxicology and Occupational Disease of a Grade A hospital in Jinan, Shandong Province, from November 2022 to June 2023. A general data questionnaire, family caring index scale, simple coping style questionnaire, and health questionnaire depression symptom group scale were used to collect the data. Pearson correlation and a structural equation model were used for data analysis. Results The average depression score of the caregivers was 5.66 ± 4.291, and the incidence of depression was 54.7%. The family function may directly or indirectly affect depression in caregivers through coping styles. Conclusion Future health education and interventions should focus on improving the family functioning of caregivers and encouraging positive coping mechanisms.